De novo transcriptome analysis of Osmanthus serrulatus Rehd. flowers and leaves by Illumina sequencing. (August 2015) - Chen, Lin; Li, Longna; Dai, Yaping; Wang, Xianrong; Duan, Yifan; Yang, Guodong
Abstract: Osmanthus serrulatus Rehd., a species endemic to China, occupies an important phylogenetic node of flowering trees, due to a different flowering season (spring) to other Osmanthus species. However, data on genetic resources are limited. In this study, we were among the first to perform de novo transcriptome sequencing for flowers and leaves of O. serrulatus using Illumina pair-end sequencing technology. Approximately 16.94 Gb of clean reads were obtained and the de novo assembly generated 92, 798 unigenes, with an average length of 697 bp. There were 2602 unigenes identified as significantly differentially expressed between flowers and leaves; among them 1306 (50.19%) were up-regulated and 1296 (49.81%) down-regulated in flowers. Metabolic pathway analysis revealed that 33 unigenes were predicted to be involved in carotenoid biosynthesis, with six genes differentially expressed between these two tissues. Our study identified genes associated with carotenoid biosynthesis in O. serrulatus and provides a valuable resource for future genomic studies on this threatened plant. Highlights: In this paper, we were among the first to perform de novo transcriptome sequencing for flowers and leaves of O. serrulatus . The carotenoid-related genes in O. serrulatus were analyzed, which will provide basic information on carotenoid biosynthesis and metabolism. The coloration mechanism of O. serrulatus may be proved by the expression of genes in the carotenoid degradation pathway.